Strategi Pengembangan Keterampilan Berbasis Teknologi dalam Pelatihan Guru - Nasution, Abdul Fattah; Munawwarah, Tarisa; Kholizah, Nur Alfiana; Sani, Dinda Aulia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research discusses technology-based skills development strategies in teacher training, aiming to improve the quality of education through the use of technology and digitalization. The research method used is a qualitative study with a literature approach. The research results show that to optimize the use of technology (IT) in teacher training, it is important to provide adequate infrastructure, including fast internet access to information and appropriate hardware. Teacher competency in utilizing technology must also be improved through relevant training, including understanding the tools and application of technology that can be used in teaching, classroom management and school-based management.